The evolution of primate coloration revisited. (30th July 2021) - Caro, Tim; Brockelsby, Kasey; Ferrari, Annie; Koneru, Manisha; Ono, Konatsu; Touche, Edward; Stankowich, Theodore
Abstract: Primates are noted for their varied and complex pelage and bare skin coloration but the significance of this diverse coloration remains opaque. Using new updated information, novel scoring of coat and skin coloration, and controlling for shared ancestry, we reexamined and extended findings from previous studies across the whole order and the five major clades within it. Across primates, we found (i) direct and indirect evidence for pelage coloration being driven by protective coloration strategies including background matching, countershading, disruptive coloration, and aposematism, (ii) diurnal primates being more colorful, and (iii) the possibility that pelage color diversity is negatively associated with female trichromatic vision; while (iv) reaffirming avoidance of hybridization driving head coloration in males, (v) darker species living in warm, humid conditions (Gloger's rule), and (vi) advertising to multiple mating partners favoring red genitalia in females. Nonetheless, the importance of these drivers varies greatly across clades. In strepsirrhines and cercopithecoids, countershading is important; greater color diversity may be important for conspecific signaling in more diurnal and social strepsirrhines; lack of female color vision may be associated with colorful strepsirrhines and platyrrhines; whereas cercopithecoids obey Gloger's rule. Haplorrhines show background matching, aposematism, character displacement, and red female genitalia where several mating partners are available. Our findings emphasize several evolutionary drivers of coloration in this extraordinarily colorful order. Throughout, we used coarse but rigorous measures of coloration, and our ability to replicate findings from earlier studies opens up opportunities for classifying coloration of large numbers of species at a macroevolutionary scale. Abstract : The reasons that primates are such a colorful group are contentious. Using a comparative approach to examine the whole order, we found evidence for coat color being driven by several protective coloration strategies; coloration being more prevalent in diurnal species; that avoidance of hybridization drives male head coloration; a possibility that pelage coloration is more diverse in species lacking female trichromatic vision; that darker species live in warm humid conditions (Gloger's rule); and colorful female genitals are associated with multiple mating. Multiple factors shape coloration in this order, and these differ across subgroups of lemurs, monkeys, and apes.